Single-molecule imaging prefusion intermediate conformations of MERS-CoV spike trimers in membrane during entry - Shuvankar Dey; Purba Pahari; Mridul Shukla; Raiees Andrabi; Dibyendu Kumar Das (Cell Reports, 2025)
Summary: Middle East respiratory syndrome coronavirus (MERS-CoV) entry into host cells is mediated by the spike (S) glycoprotein trimer. The S2 domain of spike promotes membrane fusion for MERS entry, but its mechanism of action is currently elusive. Here, we applied real-time single-molecule fluorescence resonance energy transfer (smFRET) imaging to MERS-CoV S virions to identify the prefusion intermediate states of the S2 domain on the pathway to membrane fusion and understand their role in S neutralization by S2 stem-helix-targeted neutralizing antibodies. Our observations revealed the S2 domain of unliganded MERS-CoV S to be intrinsically dynamic, with the prefusion conformation transitioning between three distinct prefusion intermediate conformations, whose relative occupancies were remodeled by receptor dipeptidylpeptidase 4 (DPP4), protease TMPRSS2, and antibody binding. Acidic pH dramatically shifts the conformational equilibrium of S2 in favor of the fusion-competent intermediate conformation. Broadly neutralizing antibodies targeting the S2 stem-helix limit the conformational transitions of S2 and inhibit the refolding of spike to the post-fusion state.